Pembuatan Kompos dan Eco Enzyme sebagai Solusi Pengolahan Sampah Organik di Desa Borobudur - Wijayanti, Sri Hapsari; Hartanti, Anastasia Tatik; Tjhintia, Veronika; Suwandhi, Adella (LP2M INSURI Ponorogo, 2023)
Many immigrants, the increasing population, and changes in the lifestyle of Borobudur (Central Java) impact the environment. One of them is waste wasting. The provision of organic trash cans and inorganic garbage cans for free in every house in the homestay village, Ngaran II Village, still has not made residents disciplined. Meanwhile, in Bumisegoro Village, the manager of the TPS3R Waste Bank has not been able to take advantage of organic waste (tempat pembuangan sampah). This activity aims to increase awareness of Ngaran II Village residents and the TPS village manager Bumisegoro Village to sort and process organic waste into compost and eco enzymes. The total number of participants was 23 people. This activity takes place from February until August 2022 through the stages of preparation, implementation, assistance, monitoring, and evaluation. Implement activities in the form of counseling on waste and its management and training on composting and eco enzymes. This activity adds to the knowledge and skills of participants. In addition, participants demonstrated their ability to make compost and eco enzymes for their use